2018
DOI: 10.1107/s2056989018015864
|View full text |Cite
|
Sign up to set email alerts
|

Four 1-aryl-1H-pyrazole-3,4-dicarboxylate derivatives: synthesis, molecular conformation and hydrogen bonding

Abstract: 1-Phenyl-1H-pyrazole-3,4-di­carb­oxy­lic acid and 1-(4-meth­oxy­phen­yl)-1H-pyrazole-3,4-dicarbohydrazide form complex hydrogen-bonded framework structures each containing multiple hydrogen-bond types, but dimethyl 1-phenyl-1H-pyrazole-3,4-di­carboxyl­ate and dimethyl 1-(4-methyl­phen­yl)-1H-pyrazole-3,4-di­carboxyl­ate form simple cyclic dimers containing only C—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is interesting that in all of these compounds, the pyrazole unit is linked to the rest of the molecule via an N atom, rather than via a C atom, as in compounds (I) and (II) reported here. We also note here the recent structure determinations for some 1-aryl-1H-pyrazole-3,4-dicarboxylate derivatives (Asma et al, 2018) and some 4,5-hydropyrazole-1-carbothioamides (Shaibah et al, 2020b).…”
Section: Tablementioning
confidence: 88%
See 1 more Smart Citation
“…It is interesting that in all of these compounds, the pyrazole unit is linked to the rest of the molecule via an N atom, rather than via a C atom, as in compounds (I) and (II) reported here. We also note here the recent structure determinations for some 1-aryl-1H-pyrazole-3,4-dicarboxylate derivatives (Asma et al, 2018) and some 4,5-hydropyrazole-1-carbothioamides (Shaibah et al, 2020b).…”
Section: Tablementioning
confidence: 88%
“…Pyrazoles exhibit a very wide range of pharmacological and other biological activities, which have recently been extensively reviewed (Ansari et al, 2017;Karrouchi et al, 2018). In a continuation of a broadly based study of the synthesis and structures of novel pyrazole derivatives (Asma et al, 2018;Kiran Kumar et al, 2020;Shaibah et al, 2020a,b), we have now investigated a three-component reaction between diethylpropanedioate (diethylmalonate), 5-chloro-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde and some aryl azides. Our expectation was that the methylene group of the ester component would undergo a condensation reaction with the carbaldehyde function to provide a new electron-deficient alkene system, which would then undergo a 1,3-dipolar cycloaddition with the aryl azide to provide pyrazole-substituted 1,2,3-triazoles.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Pyrazoles possess many pharmacological activities such as the inhibition of protein glycation, antibacterial, antifungal, anticancer, antidepressant, anti-inflammatory, antituberculosis and antioxidant activity as well as being used as antiviral agents (Fustero et al, 2011;Steinbach et al, 2000;Garcı ´a-Lozano et al, 1997). The crystal structures of (E)-1,3-dimethyl-5-p-tolyloxy-1H-pyrazole-4-carbaldehyde o-(6-chloropyridazin-3-yl)oxime (Hu et al, 2006), 1-(5-bromopyrimidin-2-yl)-3-phenyl-1H-pyrazole-4-carbaldehyde (Thiruvalluvar et al, 2007), 5-(2,4-dichlorophenoxy)-3-methyl-1-phenyl-1H-pyrazole-4carbaldehyde (Kumar et al, 2016), four 1-aryl-1H-pyrazole-3,4-dicarboxylate derivatives (Asma et al, 2018), functionalized 3-(5-aryloxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)-1-(4substituted-phenyl)prop-2-en-1-ones (Kiran Kumar et al, 2020) and two isostructural 3-(5-aryloxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)-1-(thiophen-2-yl)prop-2-en-1-ones (Shaibah et al, 2020) have been reported.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Derivatives derived from 3-amino-1H-pyrazole have been reported as tyrosine kinase inhibitors, of potential use in cancer treatment (Feng et al, 2008) and as inhibitors of the intracellular phosphorylation of the heat-shock protein hsp27 (Velcicky et al, 2010). As part of a general study of novel pyrazole derivatives (Asma et al, 2018;Kiran Kumar et al, 2020;Shaibah et al, 2020a,b;Shreekanth et al, 2020), we have now synthesized two organic salts derived from 3-amino-1Hpyrazole, namely 3-amino-1-pyrazol-2-ium 3,5-dinitrobenzoate monohydrate (I) ( Fig. 1 and Scheme) and bis(3-amino-1pyrazol-2-ium) fumarate fumaric acid (II) (Fig.…”
Section: Chemical Contextmentioning
confidence: 99%